Emotion in obesity discourse: understanding public attitudes towards regulations for obesity prevention. Issue 4 (13th November 2015) - Farrell, Lucy C.; Warin, Megan J.; Moore, Vivienne M.; Street, Jackie M.
Abstract: Intense concern about obesity in the public imagination and in political, academic and media discourses has catalysed advocacy efforts to implement regulatory measures to reduce the occurrence of obesity in Australia and elsewhere. This article explores public attitudes towards the possible implementation of regulations to address obesity by analysing emotions within popular discourses. Drawing on reader comments attached to obesity‐relevant news articles published on Australian news and current affairs websites, we examine how popular anxieties about the 'obesity crisis' and vitriol directed at obese individuals circulate alongside understandings of the appropriate role of government to legitimise regulatory reform to address obesity. Employing Ahmed's theorisation of 'affective economies' and broader literature on emotional cultures, we argue that obesity regulations achieve popular support within affective economies oriented to neoliberal and individualist constructions of obesity. These economies preclude constructions of obesity as a structural problem in popular discourse; instead positioning anti‐obesity regulations as a government‐endorsed vehicle for discrimination directed at obese people. Findings implicate a new set of ethical challenges for those championing regulatory reform for obesity prevention.